Guessing Game Method Enhances Seventh Grade Descriptive Writing Skills: Meningkatkan Keterampilan Menulis Teks Deskriptif pada Siswa Kelas Tujuh: Dampak Metode Tebak Gambar - Melinda Kartika Sari; Vidya Mandarani (Academia Open, 2023)
This study aimed to investigate the effectiveness of the Guessing Game method in improving descriptive text writing among seventh-grade students at SMPN 1 Beji. A quasi-experimental design was employed, utilizing pre-test and post-test measures in both an experimental class (7H) and a control class (7i), each consisting of 34 students. The findings revealed that the implementation of the Guessing Game method significantly enhanced students' descriptive text writing skills, as demonstrated by a t-test value of 0.003, which was below the significance level of 0.05 (0.003 < 0.05). This suggests that the Guessing Game method is an effective instructional approach for teaching descriptive text writing to seventh-grade students. The advantages of using this method include its simplicity, requiring minimal steps in writing, and its facilitation of students' ability to draw upon their prior gameplay experiences. This research provides implications for educators to employ interactive and engaging approaches, such as the Guessing Game, to foster students' writing abilities effectively. Highlights: The Guessing Game method significantly improves seventh-grade students' descriptive text writing skills. The method simplifies the writing process and incorporates students' prior gameplay experiences. Interactive and engaging approaches, like the Guessing Game, enhance student engagement and learning outcomes in writing. Keywords: Guessing Game method, descriptive text writing, seventh-grade students, quasi-experimental design, writing instruction.